Pyogenic liver abscess: contrast-enhanced ultrasound allows morpho-evolutive classification and guides personalized management - Giampiero Francica (Open Exploration Publishing Inc., 2022)
Aim: The aim of this study is to propose a contrast-enhanced ultrasound (CEUS)-based morphologic classification of pyogenic liver abscess (PLA) reflecting different evolutive stages and to assess the added value of CEUS in the management of PLA. Methods: Forty-four PLAs of different etiologies in 44 patients (male/female = 24/20; mean age 66 ± 14.7 years) were evaluated with ultrasound (US) B-mode and CEUS (using SonoVue). PLAs were mainly located in the right lobe (n = 28, 63.6%) with a mean diameter of 6.8 cm [standard deviation (SD) ± 3.2, range 1.7-15 cm]. Conventional US findings were categorized as the presence and extension of liquified areas, echogenicity and echostructure of the index lesion. Peripheral hyperenhancing rim, transient segmental enhancement, hyperenhancing septa and "honeycomb" aspect were considered PLA hallmarks in the arterial phase after contrast agent injection. CEUS results were judged as clinically relevant if they modified the approach to percutaneous treatment in comparison with pre-operative US B-mode findings. Results: CEUS was superior to US B-mode as to depiction of PLA internal echostructure and enabled identification of 4 evolutive stages of PLA: type I (tumor-like), type II ("honeycomb"), type III (multiloculated with incomplete septa), and type IV (cystic-like). In 22 cases (67.4%) out of 34 who underwent percutaneous treatment, the operator tailored percutaneous approach according to PLA internal echostructure observed during CEUS exam. Conclusions: CEUS depicts the internal structure of PLA so allowing a morpho-evolutive classification of PLA and provides invaluable information for immediately tailoring the management to the single case. By showing the structure of PLA more precisely, CEUS allows a morpho-evolutive PLA classification and guides tailored management in the single case.